2015
DOI: 10.1037/cep0000065
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect does not impact semantic retrieval failure monitoring.

Abstract: This study investigated the effect of the emotional nature of to-be-retrieved material on semantic retrieval monitoring. Across two groups, participants were either asked whether they have experienced a tip-of-the-tongue (TOT) state or to make a feeling-of-knowing (FOK) judgment. We examined the overall reporting rate as well as subjective (not accompanied by partial information recall) TOT and FOK reporting, comparing whether these differed between emotional (negatively valenced and arousing) and neutral item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Studies that induced changes in arousal through subliminal affective priming (Allen et al, 2016) and pharmacological manipulation (Hauser et al, 2017) suggested that arousal responses may reduce the tendency to adjust metacognitive judgements according to internal or external noise, although they disagreed on which aspect of metacognition (sensitivity or bias) was most affected. Additionally, some studies have reported that negatively-valenced material increased measures of confidence in perception (Koizumi, Mobbs, & Lau, 2016) and in subsequent recall (Schwartz, 2010, Zimmerman and Kelley, 2010), while others found no effect of negative valence on metacognition (D'Angelo and Humphreys, 2012, Jersakova et al, 2015). Though these studies offer mixed evidence on the relations between arousal, affect, and metacognition, they suggest that the negatively valenced and arousing qualities of nociceptive pain could alter the calibration of metacognitive judgements, perhaps yielding over-confidence in perceptual decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that induced changes in arousal through subliminal affective priming (Allen et al, 2016) and pharmacological manipulation (Hauser et al, 2017) suggested that arousal responses may reduce the tendency to adjust metacognitive judgements according to internal or external noise, although they disagreed on which aspect of metacognition (sensitivity or bias) was most affected. Additionally, some studies have reported that negatively-valenced material increased measures of confidence in perception (Koizumi, Mobbs, & Lau, 2016) and in subsequent recall (Schwartz, 2010, Zimmerman and Kelley, 2010), while others found no effect of negative valence on metacognition (D'Angelo and Humphreys, 2012, Jersakova et al, 2015). Though these studies offer mixed evidence on the relations between arousal, affect, and metacognition, they suggest that the negatively valenced and arousing qualities of nociceptive pain could alter the calibration of metacognitive judgements, perhaps yielding over-confidence in perceptual decisions.…”
Section: Introductionmentioning
confidence: 99%
“…These word-finding failures do not necessarily include the ToT state’s sense of closeness to retrieving the target word, which likely results from the achievement of partial phonological access (A. S. Brown, 1991; Jersakova, Souchay, & Allen, 2015). Thus, we hypothesize that the ToT experience does not precisely map onto the anomic experiences we describe here, but lies in between IwW and sIS at the level of partial phonological access.…”
Section: Introductionmentioning
confidence: 99%